Généralisation des expressions analytiques liées a la fonction pseudo- Voigt utilisée en analyse des profils de raies de diffraction - Hadj Larbi, F. (Array, 2009)
We revisit the theory of X-ray and neutron diffraction profile analysis relative to the pseudo-Voigt function (noted pV). We present a generalization of the analytical expressions of integral breadth and full width at half maximum of the pV function, its Fourier transform as well as the threshold limit of the mixing parameter h. The obtained results are incorporated in a fit procedure, which improves the reliability factors